An Ambulatory Care Clinic and Community Pharmacy Collaboration to Address Prescription Abandonment - Joshua W Gaborcik; Brigid K Groves; Aaron Clark; Marilly Palettas; Alexa Sevin Valentino (University of Minnesota Libraries Publishing, 2019)
Purpose: The purpose of this research is to evaluate a collaborative workflow aimed at decreasing prescription abandonment. Setting: A federally qualified health center and a 340B contracted grocery store-based community pharmacy. Practice Workflow:  An ambulatory care clinic with an established partnership with a community pharmacy chain identified a need to decrease prescription abandonment rates. A process was developed whereby an ambulatory care pharmacy technician received a report from the pharmacy of prescriptions filled for at least 7 days since the initial fill date and at risk for abandonment at the community pharmacy. The pharmacy technician identified health-system barriers, attempted to remedy any identified barriers, and conducted patient reminder phone calls. Health-system barriers were classified by the following categories: incorrect contact information at the community pharmacy, incorrect 340B copayment, incorrect insurance information at the community pharmacy, and need for prior authorization. Evaluation: A prospective cohort study was conducted from February 2016 to April 2016 in order to evaluate the effectiveness of this workflow. Results: 551 prescriptions and 350 patients were included in this cohort.  Of the 551 prescriptions, 362 had at least one identified barrier that may have led to prescription abandonment. There were 111 health-system identified barriers, and 96 of these barriers were acted upon. Additionally, there were 459 patient identified barriers, and 179 of these barriers were acted upon. When a pharmacy technician was able to identify and act upon at least one barrier, 106 prescriptions (46.9%) were picked-up from the pharmacy. Conclusion: From the information gathered in this quality improvement project, operational changes have been implemented at the ambulatory care clinic and community pharmacy as a means to further decrease modifiable health-system barriers that may lead to prescription abandonment.    Article Type: Clinical Experience